Maximise your investment : 10 key strategies for effective packaged software implementations : accelerate packaged (COTS) software implementations, increase returns on investment and reduce implementation costs and customizations /: 10 key strategies for effective packaged software implementations : accelerate packaged (COTS) software implementations, increase returns on investment and reduce implementation costs and customizations. (2009) - Unknown
No abstract available